AN INVENTION OF A SMART BLIND STICK USING IOT - A/P MUNUSAMY, MMANIYARASI; A/P LOGANATHAN, TAMIL MOLI; A/P RAMAKRISHNA, JEEVANA JOTHI (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
This paper describes an Internet of Things-based blind stick development that attempts to overcome the limitations of traditional blind sticks. The main aim is to improve security and help for people who have vision impairments. By utilizing cutting-edge technologies like Arduino, ultrasonic sensors, moisture sensors, buzzers, and rechargeable batteries, this invention tackles the problems faced by the visualized community. A proactive and dynamic navigating approach is provided by the inventive design, which combines electrical and sensor components. By giving users instant feedback on their surroundings, the obstacle detection feature encourages them to explore their surroundings in a safer and more self-assured manner. The soil moisture sensor will give the user a distinctive signal when it comes into contact with water that can be differentiated from the signal generated by an obstruction. For visually impaired people who want more mobility and independence, the blind stick with IoT (infrared or ultrasonic sensors) is a highly recommended tool. By giving users instant feedback on their surroundings, the obstacle and moisture detection functions encourage safer and more self-assured exploration of their surroundings.